2011
DOI: 10.1136/ard.2010.141598
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of spondyloarthritis and its subtypes in southern Sweden

Abstract: In Sweden the prevalence of spondyloarthritis leading to a doctor consultation is not much lower than rheumatoid arthritis. PsA was the most frequent subtype followed by AS and USpA, and the two most frequent subtypes PsA and AS also display some distinct sex patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
94
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(107 citation statements)
references
References 29 publications
12
94
1
Order By: Relevance
“…Moreover, Swedish data support a low degree of misclassification for the outcomes used in this study such as acute coronary events, where misclassification has been reported to be less than 5% (28,29). Fourth, not including patients with AS or SpA only seen in primary care may exclude approximately 15% (22) of cases possibly with milder disease. Finally, the many comparisons being undertaken yields a possibility for mass significance, and therefore some of the differences found could be attributed to a matter of coincidence.…”
supporting
confidence: 58%
See 2 more Smart Citations
“…Moreover, Swedish data support a low degree of misclassification for the outcomes used in this study such as acute coronary events, where misclassification has been reported to be less than 5% (28,29). Fourth, not including patients with AS or SpA only seen in primary care may exclude approximately 15% (22) of cases possibly with milder disease. Finally, the many comparisons being undertaken yields a possibility for mass significance, and therefore some of the differences found could be attributed to a matter of coincidence.…”
supporting
confidence: 58%
“…The study population and the frequency of medication use are as expected for patients with AS/SpA attending outpatient specialist clinics (22). Notably, the use of conventional DMARDs and glucocorticoids was rather high.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The true prevalence of PsA in the general population is not fully clear, but is reported to be 0.13-0.25% in the Nordic countries (2)(3)(4)(5). By applying classification criteria for psoriatic arthritis [ClASsification criteria for Psoriatic ARthritis (CASPAR) study] (6), the prevalence of PsA in psoriasis patients was estimated to be 13.8% (1), while other studies report a higher prevalence of 27-30% (7)(8)(9).…”
mentioning
confidence: 99%
“…Psoriatic arthritis (PsA) is a chronic inflammatory arthritis associated with the skin disorder which affects between 0.3 and 1.9% of adults [1][2][3][4][5] and causes considerable morbidity, mortality and substantially affects patient's functionality, psychology, and quality of life [6,7]. Research has shown that patients with PsA have a high risk of developing major systemic …”
Section: Introductionmentioning
confidence: 99%